HUBUNGAN STATUS AKREDITASI DENGAN TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN PUSKESMAS DI KOTA DENPASAR - Cahya Lestari, I Gusti Ayu Putu Sintya Dewi; Nopiyani, Ni Made Sri (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT The impact of the Covid-19 Pandemic has caused the quality assurance process to not run optimally, one of which is the implementation of accreditation at all health service facilities. In addition, the relationship between accreditation status and the level of satisfaction cannot be concluded because previous research is still contradictory. The purpose of this study was to measure the level of patient satisfaction and determine the relationship between accreditation status and the level of patient satisfaction. The design of this research is quantitative research with analytic cross-sectional design. The research sample selection method is non-random sampling with consecutive sampling technique, namely the sample will be selected based on the order of the patient's arrival at the earliest until the desired number of samples is met. Methods of data collection through interviews using a questionnaire instrument to measure the level of patient satisfaction. Data were analyzed using the chi-square test and multiple logistic regression. The results showed that the majority of patients expressed satisfaction as much as 57.8% and patients who stated dissatisfaction as much as 42.2%. In terms of satisfaction in each aspect of the quality dimension, the majority of patients with the highest proportion of satisfaction, namely the dimension of responsiveness and the lowest proportion of satisfaction, namely the dimension of reliability. Accreditation status is related to the level of patient satisfaction (AOR=13.7 ; 95% CI=5.40-34.5 ; P=<0.01). The sex of the patient is related to the level of patient satisfaction (AOR=3.84 ; 95% CI=1.36-10.8 ; P=<0.01). Health centers need to make improvements to aspects of service that are still considered unsatisfactory. Keywords: Accreditation, Patient Satisfaction, Public Health Center